Using the National Indonesian Growth Chart to assess short stature and obesity in urban schoolchildren in Surakarta, Indonesia: comparisons to the WHO 2007 and CDC 2000 Growth Charts - Annang Giri Moelyo; Dewinda Candrarukmi; Ulfa Puspita Rachma (Paediatrica Indonesiana, 2022)
Background The National Indonesian Growth Chart (NIGC) is a new growth chart based on Indonesian population data. To date, the CDC 2000 or WHO 2007 charts have been widely used in Indonesia to assess the growth of 5-to-18-year-old children. Use of these reference charts may lead to inaccurate conclusions about children’s nutritional status, particularly when diagnosing short stature or obesity. Objective To compare assessments of short stature and obesity in Indonesian urban schoolchildren and adolescents based on CDC, WHO, and NIGC reference charts. Methods Pooled anthropometric data [height, weight, and body mass index (BMI)] were collected cross-sectionally from healthy schoolchildren aged 6 to 18 years in Surakarta in 2013, 2016, 2018, and 2019. We created scatterplots for height, weight, and BMI and analyzed differences in height-for-age (HAZ) and BMI (BAZ) z-scores according to the CDC, WHO, and NIGC growth charts, then calculated differences in proportions of children identified as having short stature or obesity. Results We included 2,582 subjects; 63% were girls. Subjects’ mean age was 13.1 (SD 3.4) years. Mean differences in HAZ between the NIGC vs. CDC chart and NIGC vs. WHO chart were 1.44 (SD 0.01) and 1.39 (SD 0.00), respectively. Mean differences in BAZ between the NIGC vs. CDC chart and NIGC vs. WHO chart were 0.18 (SD 0.01) and 0.06 (SD 0.01), respectively. The prevalence of short stature was 9.91%, 11.62%, and 0.39% according to the WHO, CDC, and NIGC charts, respectively. The prevalence of obesity was 10.15%, 5.07%, and 11.77% according to the WHO, CDC, and NIGC charts, respectively. The prevalence of obesity according to the WHO, CDC, and NIGC was 7.44%, 2.95%, and 10.08%, respectively in girls and 14.76%, 8.69%, and 14.66%, respectively in boys. Conclusion The use of the NIGC resulted in a lower prevalence of short stature compared to the CDC or WHO charts. Compared to the WHO charts, the NIGC gave a similar prevalence of obesity overall and in boys, but a higher prevalence of obesity in girls. Compared to the CDC charts, the NIGC gave a higher prevalence of obesity both in boys and girls.